Completion of fit notes by GPs: a mixed methods study - Coole, Carol; Nouri, Fiona; Potgieter, Iskra; Drummond, Avril E.R. (SAGE, 2015)
Aims: The aim of this study was to investigate the completion of fit notes by UK general practitioners (GPs). A series of actual fit notes issued to employed patients were examined, and their GPs’ reflections and experiences of fit note completion explored.